An All-in-One Testing Chip for the Simultaneous Measurement of Multiple Thermoelectric Parameters in Doped Polysilicon - Lei Shi; Na Zhou; Jintao Wu; Meng Shi; Yizhi Shi; Cheng Lei; Haiyang Mao (Micromachines, 2025)
Polysilicon is widely used as a thermoelectric material due to its CMOS compatibility and tunability through doping. The accurate measurement of the thermoelectric parameters—such as the Seebeck coefficient, thermal conductivity, and electrical resistivity—of polysilicon with various doping conditions is essential for designing and fabricating high-performance thermopile sensors. This work presents an all-in-one testing chip that incorporates double-layer thermoelectric structures on a suspended membrane-based supporting layer, with polysilicon constituting at least one of these thermoelectric layers. By employing a differential calculation approach in conjunction with thermal imaging methods, we could simultaneously measure various thermoelectric parameters—including resistivity, the Seebeck coefficient, and thermal conductivity—of polysilicon under different doping conditions. Furthermore, the method proposed in this study provides a means for accurately obtaining thermoelectric parameters for other materials, thereby facilitating the design and optimization of thermoelectric devices.